Causes of Construction Projects Cost Overrun in Brazil - França, Alda; Haddad, Assed Naked (International Journal of Sustainable Construction Engineering and Technology, 2018)
This paper presents a survey on construction projects cost performance in Brazil with an analysis of cost overrun causes of the works based on the contractors’ point of view. After a literature review and field research, several causes were identified and evaluated by frequency, severity, and importance through a questionnaire. The field survey conducted included 11 directors, 17 project managers and 19 area managers of different construction companies. Eighty-five causes of cost overrun were identified and classified in 11 departments with internal and external influences. The research shows that 71% of the 238 contracts of the study have their costs exceeded, being 82% in amounts up to 25% of the initial agreement and 18% above 25%. The most striking causes identified by the three parties were the change of scope, lack of design detail during budgeting, and high indirect cost in a period of low productivity.